Prothrombin Complex Concentrate as a Key Adjunct in Massive Hemorrhage Management in Placenta Accreta Spectrum Disorder: A Case Report - Pramana, Putu Bagus Gin Gin; Tjokorda Gde Agung Senapathi; Pontisomaya Parami; Tjahya Aryasa (HM Publisher, 2024)
Placenta accreta spectrum disorder (PASD) is a severe obstetric complication associated with significant hemorrhage risk. This report highlights the successful use of prothrombin complex concentrate (PCC) as part of a multidisciplinary approach to managing a case of massive hemorrhage in PASD. A 36-year-old woman, G3P2002, at 33 weeks gestation, diagnosed with placenta previa totalis and suspected PASD, underwent a planned cesarean hysterectomy. The surgery was complicated by 5200 mL hemorrhage due to placental invasion and bladder injury. Hemodynamic instability was managed with massive transfusion protocol activation, including PCC, tranexamic acid, and packed red blood cells. Intra-abdominal packing was performed for hemostasis, and the bladder injury was repaired. Continued PCC administration in the ICU, along with other supportive measures, resulted in hemorrhage control and stabilization. The patient was successfully extubated and discharged after a second surgery to remove packing. This case emphasizes the vital role of PCC in the multidisciplinary management of massive hemorrhage in PASD. Early recognition of PASD risk factors and prompt intervention, including PCC administration, are crucial for optimal maternal outcomes.